IMPLEMENTASI PERILAKU UTILITARIAN MELALUI PROGRAM PEMASARAN CASHLESS CAN BE FUN BERDASARKAN KECERDASAN BUATAN - Berlian Annisa Hermawan; Endy Gunanto Marsasi (FEB Universitas Sam Ratulangi Manado, 2023)
The researcher examined one of the companies engaged in the Food and beverage retail industry in the Coffee shop field. Product distribution is carried out through offline stores and e-commerce. This research is conducted to find weaknesses and contribute by proposing a program. The method for analyzing this research is qualitative by direct observation, in-depth interviews, documentation collection, and the company's secondary data. The study was conducted through the marketing division. Based on the research conducted, it was found that the problems obtained were in the aspect of product presentation, which was considered ineffective and efficient. Based on the existing weaknesses, he contributed by proposing a program with the title Cashless Can be Fun. This program implements Artificial Intelligence with partners who work with Artificial Intelligence-based applications. This application encourages consumers to place orders and payments at the desk cashlessly. The aim is to provide comfort, satisfaction, and valuable experience to consumers, especially consumers with Utilitarian tendencies. The application of Artificial Intelligence can maximize functionality to satisfy consumers with Utilitarian tendencies.